Sterically encumbered charge-compensated carbaboranes: Synthesis and reactivity - Molecular structures of 7-Ph-11-SMe2-7,8-nido-C2B9H10 and 1-Ph-3,3-(CO2-7-SMe)(2)-3,1,2-closo-RhC2B9H8 - Rosair, G; Welch, A; Weller, A; Zahn, S (1997)
Reaction between K[7-Ph-7,8-nido-C2B9H11] and dmso in H2SO4 affords a mixture of the isomers 7-Ph-9-SMe2-7,8-nido-C2B9H10 (1a) and 7-Ph-11-SMe2-7,8-nido-C2B9H10 (1b). Similarly, starting from K[7,8-Ph2-7,8-nido-C2B9H10], the diphenyl analogue 7,8-Ph2-9-SMe2-7,8-nido-C2B9H9 (2) was produced. These three new nido carbaboranes have been characterised spectroscopically, including 11B-11B COSY and 1H-1H NOESY experiments, and by a single crystal diffraction study on 1b. Deprotonation of 1a followed by addition of [RhCl(CO)2]2 affords the carbametallaborane 1-Ph-33-(CO)2-7-SMe2-3,1,2-closo-RhC2B9H9 (3), characterised by IR and 1H and 11B NMR spectroscopies and by a crystallographic study. © 1997 Elsevier Science S.A.